Phenotypical, Clinical, and Molecular Aspects of Adults and Children With Homozygous Familial Hypercholesterolemia in Iberoamerica. Issue 10 (October 2020) - Alves, Ana Catarina; Alonso, Rodrigo; Diaz-Diaz, José Luís; Medeiros, Ana Margarida; Jannes, Cinthia E.; Merchan, Alonso; Vasques-Cardenas, Norma A.; Cuevas, Ada; Chacra, Ana Paula; Krieger, Jose E.; Arroyo, Raquel; Arrieta, Francisco; et al.
Abstract : Objective: Characterize homozygous familial hypercholesterolemia (HoFH) individuals from Iberoamerica. Approach and Results: In a cross-sectional retrospective evaluation 134 individuals with a HoFH phenotype, 71 adults (age 39.3±15.8 years, 38.0% males), and 63 children (age 8.8±4.0 years, 50.8% males) were studied. Genetic characterization was available in 129 (96%). The majority (91%) were true homozygotes (true HoFH, n=79, 43.0% children, 46.8% males) or compound heterozygotes (compound heterozygous familial hypercholesterolemia, n=39, 51.3% children, 46.2% males) with putative pathogenic variants in the LDLR . True HoFH due to LDLR variants had higher total ( P =0.015) and LDL (low-density lipoprotein)-cholesterol ( P =0.008) compared with compound heterozygous familial hypercholesterolemia. Children with true HoFH (n=34) tended to be diagnosed earlier ( P =0.051) and had a greater frequency of xanthomas ( P =0.016) than those with compound heterozygous familial hypercholesterolemia (n=20). Previous major cardiovascular events were present in 25 (48%) of 52 children (missing information in 2 cases), and in 43 (67%) of 64 adults with LDLR variants. Children who are true HoFH had higher frequency of major cardiovascular events ( P =0.02), coronary heart ( P =0.013), and aortic/supra-aortic valve diseases ( P =0.022) than compound heterozygous familial hypercholesterolemia. In adults, no differences were observed in major cardiovascular events according to type of LDLR variant. From 118 subjects with LDLR variants, 76 (64%) had 2 likely pathogenic or pathogenic variants. In 89 subjects with 2 LDLR variants, those with at least one null allele were younger ( P =0.003) and had a greater frequency of major cardiovascular events ( P =0.038) occurring at an earlier age ( P =0.001). Conclusions: There was a high frequency of cardiovascular disease even in children. Phenotype and cardiovascular complications were heterogeneous and associated with the type of molecular defect. Abstract : Supplemental Digital Content is available in the text.